(untitled) - Wolski, Bobette (Pyrmont, N.S.W., 2006)
Designed specifically for law students and new legal practitioners, this book assists in developing a range of fundamental lawyering skills and an understanding of the ethical and professional responsibilities that lawyers owe to clients, to the court and to other parties.
Keywords: Thực hành luật,Practice of law; Úc,Australia